Pengembangan Bahan Ajar Berbasis Pendekatan Open Ended Untuk Meningkatkan Keterampilan Penalaran Siswa Pada Materi Faktor Kelipatan Bilangan Di SD Negeri Pangggungroyom 01 - Ikha Valenta Nosawati; Joko Sulianto; Mira Azizah (STKIP Andi Matappa Pangkep, 2021)
The purpose of this research is to develop teaching materials on multiple factor material based on an open ended approach to improve students' reasoning abilities. This research method is RnD (Research and Development) research. The results obtained from the validation of materials and media. The results of the three material experts showed an average percentage of 86.66% and the results of the three media experts showed an average percentage of 87.57%. The results of the analysis of the fourth grade teacher response assessment obtained the results from the material assessment aspect an average percentage of 96.88% and from the media assessment aspect the average percentage got 94.45%. It can be concluded that the teaching materials developed are included in the